Pelatihan Olahan Lele Sebagai Alternatif Pemberian Makanan Tambahan (PMT) Sebagai Optimalisasi Gizi Penanganan Balita Stunting Bagi Kader Posyandu Anggrek Bulan 1 Tiyasan - Pujiastuti, Veronica Ima; Febriani, Dita Hanna (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
Posyandu cadres in Padukuhan Tiyasan Condongcatur are part of increasing the success of stunting reduction in Sleman Regency. The cadre problems are limited knowledge about stunting and nutritious food sources for toddlers and the lack of cadre skills in processing locally-based foods. This service activity's implementation methods are education, training, and mentoring. There are two main stages in implementing the program, the first stage of stunting education and an explanation of nutritious food for toddlers. The second stage is cadre training to process catfish nuggets with a "zero waste" approach. Utilization and optimization sources of regional potential are the advantages of this program. Catfish is a good animal protein source, low price, and easy to cultivate in the Tiyasan. The complete nutritional content in catfish is an alternative to high nutritional nuggets for supplementary feeding for toddlers. It can be concluded that this program is increased the knowledge of cadres about stunting and nutritious food for stunting toddlers, as well as increased the skills of cadres in processing catfish for toddlers' supplementary feeding.